ANALISIS PENGARUH KUALITAS PELAYANAN, HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN ULANG KONSUMEN PADA BENGKEL AHASS BERKAH JAYA MOTOR II - Astikaningrum Fardiani; M. Naely Azhad; Akhmad Fahrur Rozi (Makro : Jurnal Manajemen Dan Kewirausahaan, 2022)
The growing development of the automotive industry can now be seen from the number of maintenance and repair services for motor vehicles that are under the auspices of well-known product brands such as Honda. One of the workshops that stands under the auspices of Honda is Ahass Berkah Jaya Motor II. This study aims to determine the effect of (1) service quality, (2) price, (3) location on consumer repurchase decisions at Ahass Berkah Jaya Motor II workshop. The sample taken is 100 respondents using the method Purposeive Sampling. The analytical tool used to analyze the effect of service quality, price and location variables on repurchase decisions is multiple linear regression analysis with the help of statistical program SPSS for Windows v.17. The results of this study indicate that service quality has no significant effect on repurchase decisions, price has a significant positive effect on repurchase decisions, and location has a significant positive effect on repurchase decisions.